2015
DOI: 10.1002/acr.22401
|View full text |Cite
|
Sign up to set email alerts
|

Factors Explaining the Discrepancy Between Physician and Patient Global Assessment of Joint and Skin Disease Activity in Psoriatic Arthritis Patients

Abstract: Fatigue, pain, disability, and tender and swollen joint counts were the most important factors contributing to discrepancy between patient and physician assessment of joint activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 20 publications
6
76
1
4
Order By: Relevance
“…Our findings are consistent with prior smaller single-center studies that assessed factors that may influence the differences in patient-physician alignment with regard to PsA activity and control [11,18,19]. Previous studies found that patients with PsA experience a more severe burden of disease than that perceived by the physician [11,18], and nearly one quarter to a third of patients with PsA were misaligned with their physicians [11].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings are consistent with prior smaller single-center studies that assessed factors that may influence the differences in patient-physician alignment with regard to PsA activity and control [11,18,19]. Previous studies found that patients with PsA experience a more severe burden of disease than that perceived by the physician [11,18], and nearly one quarter to a third of patients with PsA were misaligned with their physicians [11].…”
Section: Discussionsupporting
confidence: 90%
“…The earlier studies found greater misalignment regarding the perception of disease activity in the joints than that of the skin symptoms (i.e., TJC, SJC vs. psoriasis, etc.) [11,18,19], possibly indicating that skin lesions are more obvious and easily perceived, so are easier to Balign^ [19]. In previous PsA studies, factors associated with misalignment were SJC, TJC, pain, and fatigue [11,18,19].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations